Bacterial community richness shifts the balance between volatile organic compound-mediated microbe–pathogen and microbe–plant interactions. Issue 1925 (29th April 2020) - Raza, Waseem; Wang, Jianing; Jousset, Alexandre; Friman, Ville-Petri; Mei, Xinlan; Wang, Shimei; Wei, Zhong; Shen, Qirong
Abstract : Even though bacteria are important in determining plant growth and health via volatile organic compounds (VOCs), it is unclear how these beneficial effects emerge in multi-species microbiomes. Here we studied this using a model plant–bacteria system, where we manipulated bacterial community richness and composition and determined the subsequent effects on VOC production and VOC-mediated pathogen suppression and plant growth-promotion. We assembled VOC-producing bacterial communities in different richness levels ranging from one to 12 strains using three soil-dwelling bacterial genera ( Bacillus, Paenibacillus and Pseudomonas ) and investigated how the composition and richness of bacterial community affect the production and functioning of VOCs. We found that VOC production correlated positively with pathogen suppression and plant growth promotion and that all bacteria produced a diverse set of VOCs. However, while pathogen suppression was maximized at intermediate community richness levels when the relative amount and the number of VOCs were the highest, plant growth promotion was maximized at low richness levels and was only affected by the relative amount of plant growth-promoting VOCs. The contrasting effects of richness could be explained by differences in the amount and number of produced VOCs and by opposing effects of community productivity and evenness on pathogen suppression and plant-growth promotion along the richness gradient. Together, these results suggest that the number of interacting bacterial species and the structure of the rhizosphere microbiome drive the balance between VOC-mediated microbe–pathogen and microbe–plant interactions potentially affecting plant disease outcomes in natural and agricultural ecosystems.